Convergent and concurrent validity of the Frankfurt Complaint Questionnaire as a screener for psychosis risk. Issue 11 (2nd November 2017) - Michel, Chantal; Kutschal, Christine; Schimmelmann, Benno G.; Schultze-Lutter, Frauke
Abstract : For the broad identification of a risk for a serious mental disorder, valid and reliable screeners are needed to detect those most likely benefitting from a time-consuming and costly in-depth clinical assessment. In the early detection of psychoses, multiple screeners for an ultra-high-risk have already been suggested. Yet, no screener explicitly targets an increased risk according to the basic symptoms (BS) criteria. We therefore explored the Frankfurt Complaint Questionnaire (FCQ) as a potential screener for BS in comparison with their gold standard clinical assessment using the Schizophrenia Proneness Instrument (SPI-A/SPI-CY) by examining its convergent (agreement between screener and gold standard, calculated by the overall percentages of agreement between FCQ and SPI-A/SPI-CY) and concurrent (degree to which a screener can identify individuals with the target condition, examined by diagnostic accuracy measures calculated using thresholds of receiver operating characteristic curves) validity. The sample consisted of 81 patients of a psychosis early detection service (41 with an at-risk mental state or psychosis, and 40 with a nonpsychotic mental disorder). Only two visual perception disturbances reached a beyond-chance level of agreement between FCQ and SPI-A/SPI-CY. For the BS criteria 'cognitive perceptive basic symptoms' and 'cognitive disturbances', only insufficient agreement between assessment techniques was detected with Cohen's kappa being 0.228 and 0.130, respectively, with an overestimation by the FCQ. Diagnostic likelihood ratios indicated only a clinically irrelevant increase in the probability of detecting BS criteria; thus, the concurrent validity of both the total of all and of only criteria-relevant FCQ items was insufficient. Both concurrent and convergent validity of the FCQ were poor, and the FCQ dramatically overestimated clinician-assessed risk. Our results suggest that the FCQ should not be used as a screener for BS criteria and that the convergent validity is not guaranteed on the basis of face validity alone, but has to be formally assessed.